Applying Social Norms Theory for Improved Nutrition Outcomes: A Case Study of JEEViKA Self Help Groups. Issue 1 (June 2021) - Lakshmi, N. Vijaya; Sinha, Irina
This paper demonstrates that malnutrition among children under the age of 5 years can be addressed by disseminating information and social and behaviour change communication. This paper discusses a social and behavioural change program implemented through a women's self-help group under JEEViKA run by the Government of Bihar.